The Role of Teachers in Integrating Islamic Character Education through the Adiwiyata Program: A Case Study at MTsN 16 Jombang - Syarifah Syarifah; Putri Adinda Ayudiyanti (Jurnal Penelitian Pendidikan, 2026)
Modernization brings new challenges to the world of education, particularly in relation to strengthening Islamic values in students. Schools are required to provide a learning process that focuses not only on cognitive aspects, but also on shaping Islamic character, which is reflected in environmental awareness, discipline, and responsibility. The Adiwiyata program is one of the strategic media that can be used to instill Islamic character values through structured and continuous activities. This study aims to describe the role of teachers in integrating Islamic character education through the Adiwiyata Program: A Case Study at MTsN 16 Jombang. The method used is a qualitative approach with a case study type through observation, interviews, and documentation. The results show that teachers play a role as role models (uswah hasanah), mentors and guides, motivators, as well as supervisors and enforcers of rules in instilling Islamic character in students. In addition, the integration of Islamic character in the Adiwiyata program is realized through general programs integrated into learning and special programs consisting of six POKJA (Working Group) components. All of these activities shape students' Islamic behavior habits, such as maintaining cleanliness, being responsible, conserving energy, and caring for the environment.